2020
DOI: 10.7759/cureus.9474
|View full text |Cite
|
Sign up to set email alerts
|

From Child Abuse to Developing Borderline Personality Disorder Into Adulthood: Exploring the Neuromorphological and Epigenetic Pathway

Abstract: Borderline personality disorder (BPD) is one of the most common personality disorders seen in the general population. Among multiple identified risk factors, one of the most influential elements is exposure to an adverse childhood experience in terms of emotional, physical, or sexual abuse. A cascade of neuromorphological and epigenetic changes occurs in response to these childhood stressors, which may have a strong link to the development of BPD. PubMed and Google Scholar were searched for articles relevant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Intense emotional responses to small stress with a greater latency for returning to baseline conditions are common in young BPD patients. Moreover, over-functioning of the prefrontal cortex generates loss of rationality, reasoning, and decision- making capacity in BPD patients ( 20 , 81 ).…”
Section: Neurobiology Neuro-morphology and Epigenetic In Early Trauma And Bpdmentioning
confidence: 99%
See 2 more Smart Citations
“…Intense emotional responses to small stress with a greater latency for returning to baseline conditions are common in young BPD patients. Moreover, over-functioning of the prefrontal cortex generates loss of rationality, reasoning, and decision- making capacity in BPD patients ( 20 , 81 ).…”
Section: Neurobiology Neuro-morphology and Epigenetic In Early Trauma And Bpdmentioning
confidence: 99%
“…Several investigators found an increase of cortisol levels (urinary, salivary, and blood) in patients with BPD, hallmarking HPA activation (78)(79)(80). The cortisol hyper-stimulation of the hippocampus can generate a distorted interpretation of signals from the environment as constant menaces, therefore sending this danger signals to amygdala, that modulates fear and aggression (20). Intense emotional responses to small stress with a greater latency for returning to baseline conditions are common in young BPD patients.…”
Section: Neurobiology Neuro-morphology and Epigenetic In Early Trauma And Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to maltreatment during childhood has long been associated with an increased risk of subsequent psychological and behavioral problems across the human lifespan including mood disorders ( Norman et al, 2012 ; Lippard and Nemeroff, 2020 ), depression ( Dhamayanti et al, 2020 ), post-traumatic stress disorder ( McLaughlin et al, 2017 ; Schuck and Widom, 2019 ), borderline personality disorder ( Mainali et al, 2020 ), adult criminality ( Minh et al, 2013 ; Kim et al, 2016 ), and drug and substance abuse ( Elwyn and Smith, 2013 ; Mandavia et al, 2016 ). Studies have demonstrated that maltreatment histories are relatively common among individuals receiving treatment for substance and drug abuse ( Funk et al, 2003 ; Banducci et al, 2014 ; Loy et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Negative childhood experiences, causing dysfunction of the HPA axis [8], can lead to some kind of PD in adults [9]. Early life stress can also induce ADs in later life through changing the status of the HPA axis.…”
Section: Introductionmentioning
confidence: 99%